LEADER MEMBER EXCHANGE, PEMBERDAYAAN KARYAWAN DAN KOMPENSASI FINANSIAL BERPENGARUH TERHADAP KEPUASAN KERJA PT. CENTRAL HERO MANUNGGAL - Nesia, Rosalina Permatasari; Dewi, I Gusti Ayu Manuati (E-Jurnal Manajemen; Vol 9 No 2 (2020)DO - 10.24843/EJMUNUD.2020.v09.i02.p11, 2020)
Employees have an important role in achieving company goals, so the company continues to develop the potential of its human resources by increasing employee job satisfaction. The purpose of this study was to analyze the influence of leader-member exchange, employee empowerment and financial compensation on job satisfaction of employees of PT. Central Hero Manunggal. The population of this study were all employees of PT. Central Hero Manunggal, which numbered 40 people, divided into Administration, Sales and Marketing, and General Affairs. Sampling in this study used a saturated sample technique or census, where the entire study population was used as samples, so the number of samples used in this study were 40 people. Data collected in this study were analyzed using multiple linear regression. The results of the analysis show that leader-member exchange, employee empowerment, and financial compensation have a positive and significant effect on employee job satisfaction at PT. Central Hero Manunggal. This means that the better the relationship between superiors and subordinates, the more employees feel empowered and the higher the financial compensation given to employees of PT. Central Hero Manunggal, the level of job satisfaction will increase. Keywords: leader-member exchange, employee empowerment, financial compensation, job                         satisfaction